Three-tiered architecture for access control in internet of medical things / Mahi Uddin - Mahi , Uddin (2022)

(untitled)
The Internet of Things (IoT) has made a successful impact on our personal and professional life. More specifically, the internet of medical things (IoMT) is capturing a crucial role in improving healthcare and providing medical facilities to human-being worldwide. Different smart sensors are connected to patients and transfer important data to the healthcare system to monitor and provide better patient treatment. As a result, the number of users is increasing drastically. Connected Internet of Things devices will be 52.2 billion by 2022. Although IoMT is counted as a promising apart in healthcare, the security of patients’ information is still a challenging issue that should be thoroughly addressed. Access control is one of the leading security mechanisms introduced to healthcare to limit access to patients’ information to only authorized individuals. In healthcare, access to the medical record of patients within a minimal time is also extremely important because less time maybe save a life. In this research, designed a three-tiered architecture for access control (T-TAFAC) on IoMT. That uses a hybrid approach by combining a fine-grained attribute-based access control model (ACM), role-based access control model (RBAC), capability-based access control model (CBAC), and using fog computing. Fog computing is a new era of cloud computing that provides computation, storage, and application services to end-users. This implemented schema is eXtensible Access Control Markup Language (XACML) driven. This T-TAFAC reduces the existing processing time. T-TAFAC is emulated as a testbed, provide a performance evaluation of this architecture, and making it compatible for practical use.